2005
DOI: 10.1194/jlr.d500018-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A sandwich enzyme-linked immunosorbent assay for human plasma apolipoprotein A-V concentration

Abstract: Apolipoprotein A-V (apoA-V) is a recently discovered apolipoprotein that appears to have a role in plasma triglyceride (TG) transport. We have developed an ELISA for apoA-V using monoclonal antibodies that has a lower limit of detection of 0.3 ng/ml and linearity up to 20 ng/ml. The ELISA was then used to quantify plasma apoA-V in 196 healthy subjects and 106 patients with insulin-resistant diabetes mellitus. In the healthy subjects, total apoA-V concentration was 179.2 ؎ 74.8 ng/ml, and it was greater in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
5
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 44 publications
8
82
5
2
Order By: Relevance
“…In contrast, all VLDL particles are carrying one or more APOC3 molecules. Average plasma APOA5 levels have been reported in healthy normolipidaemic volunteers of Caucasian origin as 16 μg/100 ml [19] and 1 μg/100 ml [22], and in healthy Japanese subjects as 18 μg/100 ml [17]. In our patients with type 2 diabetes, who were of Caucasian origin and had moderately elevated plasma triglyceride levels, plasma APOA5 levels were 7 to 139 μg/100 ml.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In contrast, all VLDL particles are carrying one or more APOC3 molecules. Average plasma APOA5 levels have been reported in healthy normolipidaemic volunteers of Caucasian origin as 16 μg/100 ml [19] and 1 μg/100 ml [22], and in healthy Japanese subjects as 18 μg/100 ml [17]. In our patients with type 2 diabetes, who were of Caucasian origin and had moderately elevated plasma triglyceride levels, plasma APOA5 levels were 7 to 139 μg/100 ml.…”
Section: Discussionmentioning
confidence: 49%
“…270-0003, Bio-Rad, Richmond, CA, USA). Plasma APOA5 concentration was measured using a recently developed sandwich ELISA as described [17]. The monoclonal antibody B10E was used for capture and biotinylated monoclonal antibody E8E was used for detection.…”
Section: Study Protocolmentioning
confidence: 99%
“…3 Single nucleotide polymorphisms (SNPs) in this gene, such as rs662799 (À1131T4C), have been reported to be associated with hypertriglyceridaemia in Caucasians and Asians. [3][4][5][6] It is not clear if other SNPs in APOA5 might also be related to triglyceride level. Therefore, we investigated the relationship between tagging SNPs in the APOA5 gene with triglyceride level in the Hong Kong Cardiovascular Risk Prevalence Study and confirmed the results in a larger group of subjects from the Guangzhou Biobank Cohort Study.…”
Section: Introductionmentioning
confidence: 99%
“…3 The plasma level of apo A5 correlates positively with high-density lipoprotein (HDL) cholesterol, but negatively with triglycerides. 4 It is lower in men and patients with diabetes. 4 In man, the APOA5 gene is located on chromosome 11q23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation